Growth Improvement of Palm Oil Seedling using Biochar from Oil Palm Empty Fruit Bunch and Rubber Wood - Seldi Prayoga; Melya Riniarti; Hendra Prasetia; Kukuh Setiawan; Samsul Bakri; Wahyu Hidayat (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Agricultural wastes biochar can be used to support the growth of oil palm seedlings. This study aims to assess the effectiveness of biochar pellets made from oil palm empty fruit bunches (OPEFB) and rubber wood wastes on the growth of oil palm seedlings. The research was conducted in the greenhouse using a factorial complete randomized design with two treatment factors, namely the type of biochar pellets (OPEFB and rubber wood) and doses of 0%, 5%, 10% with 10 replications. Observation included plant height, stem diameter, number of leaves, and total dry weight. The results showed that biochar pellet application had a significant effect on plant growth, especially at a 10% dose, which increased plant height, stem diameter, number of leaves, and dry weight compared with the control. The 10% dose of OPEFB biochar pellet produced a plant height of 21.4 cm, stem diameter of 3.64 cm, and number of leaves of 8 strands, while the same dose of rubber wood biochar pellet produced a height of 15.67 cm, diameter of 3.64 cm, and number of leaves of 6.67 strands. OPEFB biochar pellet showed higher results than rubber wood biochar, but at the same dose, the difference is minor. These results indicate that biochar pellets from agricultural waste have the potential to effectively support the growth of oil palm seedlings in an environmentally friendly manner.